Pelaksanaan Perlindungan Hukum Terhadap Anak Korban Sebagai Saksi Tindak Pidana Pencabulan di Wilayah Hukum Kejaksaan Negeri Agam - Reza Tri Putra Aldrin; Aria Zurnetti; Nilma Suryani (UNES Law Review, 2024)
Children need special protection to maintain their dignity and dignity, in accordance with the objectives of the Criminal Justice System in the Juvenile Criminal Justice System. The Prosecutor's Office and other child protection institutions as part of the criminal justice sub-system, play a role in helping and protecting child victims as witnesses in trials. According to Article 1 Number 8 of Law of the Republic of Indonesia Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning the Protection of Witnesses and Victims, namely Protection is all efforts to fulfill rights and provide assistance to provide a sense of security to Witnesses and/or Victims which must be carried out by the Witness and Victim Protection Institute (LPSK) or other institutions in accordance with the provisions of this Law. The problem is that in one of the cases in the jurisdiction of the Agam District Prosecutor's Office, on the agenda of the witness examination (evidence) at the Lubuk Basung District Court, the victim's child's statement as a witness is different from the information in the Examination Report (BAP) in the case file made by the West Sumatra Police Investigator. This caused the defendant to be acquitted by the Lubuk Basung District Court Judge who was previously prosecuted by the Public Prosecutor for 15 (fifteen) years. Therefore, the defendant was proven innocent because the victim's child's testimony as a witness could not convince the judge that the defendant had committed a criminal act of obscenity. In this case, it can be seen whether the victim's child received intervention from another party when he became a witness so that his statement at trial was different from the information in the Examination Report (BAP) in the case file. The formulation of the problems discussed in this study is 1. How is the implementation of legal protection for child victims as witnesses to criminal acts of abuse in the jurisdiction of the Agam District Attorney's Office 2. What are the obstacles faced by the Prosecutor in implementing legal protection for child victims as witnesses to criminal acts of abuse in the jurisdiction of the Agam District Attorney's Office? The research method used is empirical legal research (empirical juridical) which is supported by research in the Jurisdiction of the Agam District Attorney's Office. The results of the study show that the implementation of legal protection for child victims as witnesses to criminal acts of abuse in the jurisdiction of the Agam District Prosecutor's Office has been accompanied by professional social workers, but the legal protection for the victim's child has not been maximized because there is still intervention from certain parties so as to affect the victim's child's testimony in the trial. The obstacle faced by the prosecutor is that the victim's child is limited in providing Testimony, the public prosecutor found it difficult to prove the charges at trial, the defendant did not admit to his actions. This makes it difficult for the Public Prosecutor to prove at trial and carry out legal protection for the victim's child as a witness.